2018
DOI: 10.1177/1086296x18784699
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Neocolonial Epistemologies: Decolonizing Research Toward Transformative Literacy

Abstract: As literacy research moves across physical and cultural boundaries, populations, languages, and so forth, current policies and practices influence new research with Indigenous populations. In the last Journal of Literacy Research (JLR) issue, Keehne, Sarsona, Kawakami, and Au (2018) raised many critical ideas and shared an indigenous framework about Hawaii schools to explore culturally responsive instruction. To extend a focus on Indigenous populations, we asked Bekisizwe Ndimande to address the question: "Wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Such widespread underrepresentation can lead to the mischaracterization of non-Westerners as lacking or deficient-without regard to the limitations and ethics of doing so. In keeping with Indigenous ethics that value and expect community consultation and involvement, Ndimande (2018) suggested that literacy research "by" or "on" so-called others should instead engage with others' languages, and perhaps align with non-Western cultural norms and practices.…”
Section: Literacy and The Sociopolitical Milieu Governing Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Such widespread underrepresentation can lead to the mischaracterization of non-Westerners as lacking or deficient-without regard to the limitations and ethics of doing so. In keeping with Indigenous ethics that value and expect community consultation and involvement, Ndimande (2018) suggested that literacy research "by" or "on" so-called others should instead engage with others' languages, and perhaps align with non-Western cultural norms and practices.…”
Section: Literacy and The Sociopolitical Milieu Governing Scholarshipmentioning
confidence: 99%
“…Certainly, literacy educational research journals such as JLR and RRQ are beginning to publish more articles offering sociocultural perspectives focused upon global issues, including global ethics and epistemologies, cosmopolitanism, transliteracies, bordercrossing, translanguaging, pluraversity, and global meaning-making (e.g., García & Kleifgen, 2020;Gutiérrez, 2008;Hull & Stornaiuolo, 2014;Kim, 2016;Lam et al, 2012;Ndimande, 2018;Perry, 2021;Rizvi, 2009;Stornaiuolo et al, 2017;Tierney, 2018bTierney, , 2020Wandera, 2020). Therefore, optimistically, I would suggest that changes are looming; as a critical global advocate, I would posit that we are not there yet.…”
Section: Literacy and The Sociopolitical Milieu Governing Scholarshipmentioning
confidence: 99%
“…Moreover, this oversight perpetuates a long-standing "common understanding which suggests that Asia and the Pacific are 'over there,' outside of and apart from what is considered 'American'" (Coloma, 2006, p. 11). Rendering invisible Asia, the Pacific Islands, and peoples of their diasporas contributes to the perseverance of an occidental perspective-one that undermines efforts to decolonize research and honor different ways of understanding the world (Ndimande, 2018).…”
Section: What (And Who) Counts In Literacy Research and Educationmentioning
confidence: 99%
“…Decolonizing education refers to critiquing and questioning colonizers’ views of what counts as knowledge, who gets to determine what is important to learn and how, and the dominance of western ways of education on indigenous peoples (Chilisa, Major, & Khudu‐Petersen, 2017; McGregor & Marker, 2018). It means understanding the historical issues in a community and inquiring about a group's perspectives of schooling and teaching (Ndimande, 2018). Ndlovu‐Gatsheni (2018) detailed how western education destroyed indigenous peoples’ ways of knowing and damaged indigenous languages and cultures, positioning itself as the maker of knowledge, demoting all other ways of knowing.…”
Section: Decolonizing Educationmentioning
confidence: 99%